2017
DOI: 10.35609/afr.2017.2.4(3)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of IFRS Convergence on Earnings Quality: Empirical Evidence from Indonesia

Abstract: Objective - The purpose of this research is to examine the impact of the International Financial Reporting Standard (IFRS) convergence in Indonesia on earnings quality. Methodology/Technique - Earnings quality is measured on both accrual earnings management and real earnings management. Indonesia began convergence IFRS in 2012. IFRS is considered capable of improving comparability, transparency, and earnings information, which is expected to ultimately improve earnings quality. The sample in this research use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This position is in line with previous studies, including Kusumaningwedari & Oktorina (2017), Kristanto et al (2014), andHouqe et al (2011), which the findings generally showed that IFRS convergence does not effect on quality of earnings. However, other studies did not support this position, such as Almaharmeh & Masa'deh (2018), Sutrisno & Djashan (2017), Syarif & Pasaribu (2015), and Ismail et al (2013), which the findings generally revealed that IFRS convergence has effect on earnings quality.…”
Section: Ifrs Convergence and Earnings Qualitymentioning
confidence: 87%
See 4 more Smart Citations
“…This position is in line with previous studies, including Kusumaningwedari & Oktorina (2017), Kristanto et al (2014), andHouqe et al (2011), which the findings generally showed that IFRS convergence does not effect on quality of earnings. However, other studies did not support this position, such as Almaharmeh & Masa'deh (2018), Sutrisno & Djashan (2017), Syarif & Pasaribu (2015), and Ismail et al (2013), which the findings generally revealed that IFRS convergence has effect on earnings quality.…”
Section: Ifrs Convergence and Earnings Qualitymentioning
confidence: 87%
“…Studies carried out by Almaharmeh & Masa'deh (2018) and Sutrisno & Djashan (2017) found that IFRS convergence affects earnings quality. Inggrid & Wardhani (2011) discovered that during the high season of demand for converting accounting standards to IFRS, the convergence has been proved as capable to increse company earnings quality.…”
Section: Page179 Page179mentioning
confidence: 97%
See 3 more Smart Citations